DEVELOPMENT OF ARTICULATE STORYLINE INTERACTIVE LEARNING MEDIA TO SUPPORT BASIC ACCOUNTING LEARNING FOR CLASS X - Nur Faizahain, Nur Faizahain; Rochmawati (Jurnal Pendidikan Ilmu Sosial, 2024)
This research aims to explain the media development process, determine the feasibility and response of students to the development of articulate storyline based interactive learning media as a support for basic accounting learning in class X Accounting and Finance students at SMK Negeri 1 Surabaya. The development model used in this research is ADDIE. The research instruments include material expert validation sheets, media expert validation sheets, language expert validation sheets, and student response questionnaires. The validation results from material, media and language experts respectively received a percentage of 94%, 95% and 99% with the "very appropriate" criteria, while student responses reached 97% with the "very understand" criteria. Thus, it can be concluded that articulate storyline-based interactive learning media is suitable for use in the learning process.